Penilaian kepuasan pengguna terhadap penggunaan sistem rangkaian komputer berteknologi kluster di unit perancang ekonomi - Suhaila Zainudin; Khairuddin Omar; Johari Hasim; Aziz Deraman; Hazilah Mohd Amin (Penerbit UKM, 2004)
Cluster technology is a technology used to develop local area network systems with high availability. The utilization of cluster technology in local area network will affect users in terms of effectiveness, efficiency and system availability. The success of the system depends on the users’ acceptance and satisfaction towards the system. This study will evaluate users’ satisfaction on the use of cluster technology in local area network systems. The study is important because the utilization of cluster technology in the local area network systems is still new especially for personal computer users. A research model was used by including technical service aspect as an important factor for the success of the system. A questionnaire was developed to gather information regarding users’ expectations on systems and its services. Results showed that the use of cluster technology has been successful in reducing system downtime and has increased users’ satisfaction and acceptance of the system